Moiré band structure engineering using a twisted boron nitride substrate - Xirui Wang; Cheng Xu; Samuel Aronson; Daniel Bennett; Nisarga Paul; Philip J. D. Crowley; Clément Collignon; Kenji Watanabe; Takashi Taniguchi; Raymond Ashoori; Efthimios Kaxiras; Yang Zhang; et al. (Nature Communications)
Abstract Applying long wavelength periodic potentials on quantum materials has recently been demonstrated to be a promising pathway for engineering novel quantum phases of matter. Here, we utilize twisted bilayer boron nitride (BN) as a moiré substrate for band structure engineering. Small-angle-twisted bilayer BN is endowed with periodically arranged up and down polar domains, which imprints a periodic electrostatic potential on a target two-dimensional (2D) material placed on top. As a proof of concept, we use Bernal bilayer graphene as the target material. The resulting modulation of the band structure appears as superlattice resistance peaks, tunable by varying the twist angle, and Hofstadter butterfly physics under a magnetic field. Additionally, we demonstrate the tunability of the moiré potential by altering the dielectric thickness underneath the twisted BN. Finally, we find that near-60°-twisted bilayer BN also leads to moiré band features in bilayer graphene, which may come from the in-plane piezoelectric effect or out-of-plane corrugation effect. Tunable twisted BN substrate may serve as versatile platforms to engineer the electronic, optical, and mechanical properties of 2D materials and van der Waals heterostructures.